Youth to senior football: A season long case study of goal scoring methods between under 16, under 18 and first team - Smith, S.; Callaway, A. J.; Broomfield, S. A. (International Journal of Performance Analysis in Sport, 2013)
Goal-scoring is the pinnacle of any football match, analysis of the methods used provide insight into the way teams attack. Despite heavy research at senior level there is a dearth of literature surrounding the youth game. The purpose of this study was to compare goal scoring methods at youth and senior level. Goal-related data was derived from competitive matches involving the first team, u18s and u16s. Results showed differences between groups for number of actions (F2,242=3.401, p=.035) and percentage of forward actions (F2,225=3.201, p=.043). Build-up duration was not different between groups (F2,242=1.567, p=.211). There was a difference between the assist areas used between all teams (H2= 7.737, p = .021). Post-hoc analysis showed no differences between the assist actions used between any teams (H2 = 2.112, p = .348), but there were differences with the assist area. Each team favoured different assist actions (1st team = cross, u18s = pass, u16s = dribble). The differences between teams are attributed to factors such as experience, tactical/technical skills, perceptual abilities and level of pressure. Training implications for youth teams include developing a more elaborate style of attack and utilisation of the whole pitch when attacking.